Impact of the Number of Levels on Adverse Events and Length of Stay Following Posterior Lumbar Fusion Procedures. Issue 3 (April 2019) - Bohl, Daniel D.; Haws, Brittany E.; Khechen, Benjamin; Patel, Dil V.; Mayo, Benjamin C.; Ahn, Junyoung; Louie, Philip K.; Cardinal, Kaitlyn L.; Guntin, Jordan A.; Singh, Kern
Abstract : Study design: Retrospective Summary of background data: Little is known regarding the impact of the number of operative levels on the risk for adverse events following spinal procedures. Objective: The objective of this study was to test for associations between the number of operative levels and occurrence of adverse events following posterior lumbar fusion (PLF). Methods: Patients undergoing 1-, 2-, or 3-level PLFs were identified in the American College of Surgeons National Surgical Quality Improvement Program database. The number of operative levels was tested for association with occurrence of adverse events in the 30-days following the procedure using multivariate regression. Post hoc pairwise comparisons were made between 1- and 2-level and between 2- and 3-level procedures. Analyses were adjusted for differences in baseline characteristics. Results: In total, 8162 underwent 1-level, 3, 527 underwent 2-level, and 718 underwent 3-level procedures. Patients undergoing 2-level procedures had a higher rate of anemia requiring blood transfusion than 1-level procedures (23.4% vs. 8.6%; adjusted relative risk [RR]=2.5; P <0.001). Furthermore, patient undergoing 3-level procedures had a higher rate of anemia requiring blood transfusion than 2-level procedures (29.9% vs. 23.4%; adjusted RR=1.3; P <0.001). In addition, patients undergoing 3-level procedures had a longer length of stay than 2-level procedures (4.6 vs. 3.9 d; P <0.001) and 2-level procedures had a longer length of stay than 1-level procedures (3.9 vs. 3.5 d; P <0.001). Conclusions: Increasing the number of operative levels by one level has minimal impact on the rates of most short-term postoperative adverse events following PLF. This is true both for an increase from 1 to 2 levels and from 2 to 3 levels. While surgeons should consider that an increase in the number of operative levels may increase the risk for blood transfusion and will almost certainly prolong the hospital stay, they need not fear a major increase in the rates of postoperative adverse events. Abstract : Supplemental Digital Content is available in the text.